Problematic aspects of studying the impact of criminal activity among illegal migrants on organised crime - O. Dzhuzha; V. Vasylevych; V. Sіuravchyk (Юридичний часопис Національної академії внутрішніх справ)
The relevance of this article is justified by the need to analyse the problematic aspects of studying the link between criminal activity among illegal migrants and organised crime. This study aimed to conduct a comprehensive examination of international experience in preventing criminal offences committed by illegal migrants. To achieve this aim, the research employed general and specialised scientific methods, including analysis, synthesis, classification, and grouping, which facilitated the examination of a broad spectrum of academic discussions on the issue. A review of the scholarly literature enabled a critical analysis of the prevailing discourse on the erosion of distinctions between legality and illegality and the decriminalisation of unacceptable behaviour, particularly concerning illegal migrants. The analysis of research findings indicated that criminologists should prioritise the development of an effective state strategy for addressing crime, particularly that involving illegal migrants. Such a strategy would enable the optimal allocation of societal resources for countering criminal manifestations associated with illegal migration. It has been established that a significant obstacle to developing a scientific foundation and formulating such a policy is the lack of objective data, that would enable the construction of an accurate criminological profile of this social group. This is due to the fragmented nature of research on this subject and the absence of studies providing a comprehensive assessment of criminal activity among illegal migrants within specific states or large administrative units. The findings of this study may be applied in practice by governmental authorities to enhance migration policy and by law enforcement agencies to prevent criminal activity among illegal migrants